Asian patients versus non-Asian patients in the efficacy and safety of direct oral anticoagulants relative to vitamin K antagonist for venous thromboembolism: A systemic review and meta-analysis. Issue 166 (June 2018) - Yamashita, Yugo; Morimoto, Takeshi; Toyota, Toshiaki; Shiomi, Hiroki; Makiyama, Takeru; Ono, Koh; Kimura, Takeshi
Abstract: Introduction: The standard for treatment and secondary prevention of venous thromboembolism (VTE) has been vitamin K antagonist (VKA), which might be associated with a higher risk of bleeding particularly in Asian patients. Direct oral anticoagulants (DOAC) have been shown to be safer alternatives for VTE. It remains unclear whether this is the case in Asian ethnicity. Materials and methods: We performed a meta-analysis of randomized controlled trials to evaluate the efficacy and safety of DOACs in Asian and non-Asian patients with acute VTE. We searched MEDLINE, CENTRAL, andClinicalTrials.gov . The efficacy endpoint was recurrent VTE or VTE-related death. The safety endpoint was major bleedings or clinically relevant non-major bleedings. The pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated. Results: We identified 6 studies that comprised 3542 Asian and 23, 481 non-Asian patients. The efficacy of DOACs was comparable with VKA in both Asian and non-Asian patients (OR, 0.90; 95% CI, 0.55–1.49; P = 0.69 for Asian patients; OR, 0.92; 95% CI, 0.78–1.08; P = 0.32 for non-Asian patients; P interaction = 0.94). DOACs significantly reduced the safety endpoint compared with VKA in Asian patients (OR, 0.64; 95% CI, 0.51–0.80; P < 0.001), while DOACs were associated with non-significant reduction in non-Asian patients (OR, 0.73; 95% CI, 0.53–1.01; P = 0.06), indicating that the reduction seemed numerically more prominent in Asian patients, although there was no statistically significant interaction ( P interaction = 0.49). Conclusions: The efficacy of DOACs was comparable with VKA irrespective of ethnicity, and DOACs could be safer alternatives in Asian patients. Highlights: The efficacy of DOACs was comparable with VKA in both Asians and non-Asians. DOACs significantly reduced the safety endpoint compared with VKA in Asians. DOACs were associated with non-significant reduction in the safety in non-Asians. DOACs was safer compared with VKA, which seemed numerically more prominent in Asians.